Safety and efficacy of long-term nicotinamide mononucleotide supplementation on metabolism, sleep, and nicotinamide adenine dinucleotide biosynthesis in healthy, middle-aged Japanese men - Yamaguchi, Shintaro; Irie, Junichiro; Mitsuishi, Masanori; Uchino, Yuichi; Nakaya, Hideaki; Takemura, Ryo; Inagaki, Emi; Kosugi, Shotaro; Okano, Hideyuki; Yasui, Masato; Tsubota, Kazuo; Hayashi, Kaori; et al. (ENDOCRINE JOURNAL, 2024)
Obesity and aging are major risk factors for several life-threatening diseases. Accumulating evidence from both rodents and humans suggests that the levels of nicotinamide adenine dinucleotide (NAD+), a regulator of many biological processes, declines in multiple organs and tissues with aging and obesity. Administration of an NAD+ intermediate, nicotinamide mononucleotide (NMN), replenishes intracellular NAD+ levels and mitigates aging- and obesity-associated derangements in animal models. In this human clinical study, we aimed to investigate the safety and effects of 8-week oral administration of NMN on biochemical, metabolic, ophthalmologic, and sleep quality parameters as well as on chronological alterations in NAD+ content in peripheral tissues. An 8-week, single-center, single-arm, open-label clinical trial was conducted. Eleven healthy, middle-aged Japanese men received two 125-mg NMN capsules once daily before breakfast. The 8-week NMN supplementation regimen was well-tolerated; NAD+ levels in peripheral blood mononuclear cells increased over the course of NMN administration. In participants with insulin oversecretion after oral glucose loading, NMN modestly attenuated postprandial hyperinsulinemia, a risk factor for coronary artery disease (n = 3). In conclusion, NMN overall safely and effectively boosted NAD+ biosynthesis in healthy, middle-aged Japanese men, showing its potential for alleviating postprandial hyperinsulinemia.